An easy-to-prepare mini-scaffold for DNA origami. Issue 40 (28th September 2015) - Brown, S.; Majikes, J.; Martínez, A.; Girón, T. M.; Fennell, H.; Samano, E. C.; LaBean, T. H.
Abstract : A system is described for easy ssDNA production; folding of the 2404-base scaffold into several DNA origami shapes is demonstrated. Abstract : The DNA origami strategy for assembling designed supramolecular complexes requires ssDNA as a scaffold strand. A system is described that was designed approximately one third the length of the M13 bacteriophage genome for ease of ssDNA production. Folding of the 2404-base ssDNA scaffold into a variety of origami shapes with high assembly yields is demonstrated.